Measurement of the cosmic-ray energy spectrum above 2.5×1018 eV using the Pierre Auger Observatory - Dova M.T. (2020)
We report a measurement of the energy spectrum of cosmic rays for energies above 2.5×1018 eV based on 215,030 events recorded with zenith angles below 60°. A key feature of the work is that the estimates of the energies are independent of assumptions about the unknown hadronic physics or of the primary mass composition. The measurement is the most precise made hitherto with the accumulated exposure being so large that the measurements of the flux are dominated by systematic uncertainties except at energies above 5×1019 eV. The principal conclusions are(1) The flattening of the spectrum near 5×1018 eV, the so-called "ankle,"is confirmed.(2) The steepening of the spectrum at around 5×1019 eV is confirmed.(3) A new feature has been identified in the spectrum: in the region above the ankle the spectral index γ of the particle flux (∝E-γ) changes from 2.51±0.03 (stat)±0.05 (syst) to 3.05±0.05 (stat)±0.10 (syst) before changing sharply to 5.1±0.3 (stat)±0.1 (syst) above 5×1019 eV.(4) No evidence for any dependence of the spectrum on declination has been found other than a mild excess from the Southern Hemisphere that is consistent with the anisotropy observed above 8×1018 eV. © 2020 authors. Published by the American Physical Society.